Implementasi Strategi Komunikasi dalam Membangun Personal Branding di YouTube: Studi Literatur pada Kreator Gaming Mikro bioplazee - Restu Agung Setyo Nugroho; Viro Dharma Saputra (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study explores the implementation of communication strategies in building personal branding on YouTube, with a particular focus on the micro-gaming content creator bioplazee. Using a qualitative approach, this research adopts a systematic literature review method by analyzing scientific journals, academic books, and other relevant sources published within the last five years. In addition, empirical analysis is conducted on the bioplazee YouTube channel to observe real-world applications of communication and branding practices. The study finds that communication strategies serve as a fundamental component in shaping audience perceptions, fostering engagement, and differentiating content creators in an increasingly competitive digital space. For micro-creators with limited resources (352 subscribers), authenticity and local cultural elements—such as using a Javanese accent and adapting to trending game themes—are found to be powerful tools for building a unique identity. However, the research also identifies gaps between theoretical models and practical execution, especially in maintaining message consistency, systematic content planning, and collaborative networking. These findings emphasize the importance of developing more structured, adaptive, and sustainable communication strategies for micro-creators to strengthen their personal branding, attract a loyal audience base, and achieve long-term growth in the dynamic landscape of digital content creation.